Pain : psychological perspectives - Hadjistavropoulos, Thomas; Craig, Kenneth D., 1937- (Lawrence Erlbaum, 2004)
This volume offers a comprehensive account of the psychology of pain that encompasses not only clinical perspectives but also basic social and behavioural science, as well as biopsychological contributions to the field.